PO132 Clinical features of demyelination following anti-tnfΑ therapy. (1st December 2017) - Hendy, Peter; Heerasing, Neel; Walker, Gareth; Goodhand, James; Harrower, Tim; Hobart, Jeremy; Spiers, Alexander; Coles, Alasdair; Martin, Roswell; Ahmad, Tariq
Abstract : Background: Anti-TNFα therapy has been associated with demyelination in clinical trials and small case series although the specific clinical features and outcomes have not been reported. Methods: An expert panel assessed causality from report forms. Probable cases required a consistent history and examination conducted by a neurologist and radiological ±electrophysiological evidence of demyelination. Definite cases required a positive rechallenge. Results: 54 cases were recruited from 28 hospitals. 35 (24 female) were definite/probable. Adalimumab, Infliximab, Etanercept, and Certolizumab were implicated. Average age was 40 (95%CI 37–44) years and mean treatment duration 27 (95%CI 18–36) months. 22 cases (63%) presented with brain ±spinal lesions, 8 (23%) spine only, 5 (14%) peripheral demyelination. After drug withdrawal patients were followed for a mean 42 (95%CI 32–52) months. Of those with CNS lesions, 11/30 (37%) developed a relapsing demyelinating syndrome or Multiple Sclerosis (MS). Only 5/30 (17%) had complete symptom resolution after a mean 419 days (95% CI 36–802). Conclusion: This case series details the clinical features of demyelination following anti-TNFα therapy. Consistent with MS, young females are over-represented. Complete recovery is uncommon. Over one third develop a relapsing illness/MS. We aim to enlarge this cohort to explore genetic markers that identify at-risk patients.